Kravet på kreditprövning i kampen mot överskuldsättningen - Gedda,Elinor (2024)
Credit serves as a fundamental pillar of modern consumer-driven economies, empowering individuals to finance substantial purchases that would otherwise be unattainable. However, excessive borrowing carries risks, as consumers may accumulate debts they cannot repay, leading to over-indebtedness. This issue has both personal and societal consequences: individuals may experience severe financial distress, mental health struggles, and an increased risk of suicidal thoughts. On a broader scale, over-indebtedness is associated with economic instability and increased productivity losses. The consumer credit market has evolved considerably in recent decades, introducing new lenders and credit products, which in turn pose new regulatory challenges. This graduate thesis critically examines the effectiveness of the creditworthiness assessment requirement under Section 12 of the Consumer Credit Act. The provision was introduced to mitigate the risks of over-indebtedness and to emphasize the creditor’s responsibility in ensuring that consumers do not take on excessive debt beyond their financial capacity. The assessment must be based on sufficient information about the consumer’s financial situation, and creditors are expected to determine repayment ability with a high degree of certainty. However, the legal framework does not specify in detail what constitutes "sufficient information", leading to varying interpretations among creditors, regulatory authorities, and courts. Creditors must decide on a case-by-case basis what information to collect and how to conduct the assessment. Typically, this process involves obtaining a credit report, and consumers are often required to provide additional information. Despite the legal requirement, creditworthiness assessments remain inconsistent, often failing to prevent irresponsible lending. Creditors do not have access to comprehensive financial data, making it difficult, if not impossible, to accurately assess a consumer’s total income, expenses, and existing debts. This gap in information leads to inconsistencies in how credit is granted and increases the risk of loans being issued to individuals who are unable to repay them. In addition, business models vary widely among creditors, with some lenders specifically targeting high-risk consumers. It is almost impossible for a consumer to challenge a credit agreement other than by paying for it; agreements must be honored. The consumer is therefore the one who bears the financial burden if a creditor carries out an inadequate assessment. The thesis presents four possible legislative and regulatory proposals aimed at strengthening the creditworthiness assessment framework, either for near-term implementation or for future consideration. One proposed reform is the repeal of the Certain Consumer Credit-related Operations Act, which could enhance the accuracy of creditworthiness assessments by addressing existing regulatory gaps. However, this measure may be excessively broad in scope, raising concerns about proportionality. Another proposal involves the adoption of a new Consumer Credit Act, incorporating more detailed provisions from the Consumer Credit Directive on how creditworthiness assessments should be conducted. While this would provide clearer guidelines, some flexibility remains, leaving room for continued variation in interpretation. The possibility of introducing a civil penalty provision has also been considered, which could enhance consumer protection and incentivize lenders to conduct more thorough credit assessment. Additionally, the establishment of a national debt and credit information register has been proposed to improve the accuracy of assessments by ensuring that all creditors have access to correct financial data on consumers' financial situations. While such a register could lead to more reliable credit decisions, it also raises concerns regarding consumer privacy rights. In conclusion, while the current legal framework aims to prevent over-indebtedness, its practical implementation is inadequate due to gaps in data access and inconsistencies in interpretation. The proposed legislative changes could improve the accuracy and effectiveness of creditworthiness assessments, but each reform also presents legal challenges that must be carefully considered.
Keywords: bankrätt; finansrätt; förmögenhetsrätt